The prevalence of social phobia in a group of high school students: A field study in high schools in the city of Erbil - Omar Hama Ahmed; Sabah Ahmed Muhammad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This research intends to measure the prevalence of social phobia in a sample of high school students, as well as knowing the variations among the research variables, such as gender (male and female); school type (public or private); Study type (literary and scientific); The level of living (lower, medium, or high), The research was designed using a descriptive analytic approach a social survey sample. Participated in a high school study (400 units) in which a scale to measure social phobia was developed by the researcher. The statistical package for social sciences (SPSS) was used to analyze the data. According to the research’s findings, 22.5% of the research sample had social anxiety, which is low when compared to other studies. Additionally, the variable doesn’t make a difference: Gender; type of school; type of education; However, there are differences in the standard of living (lower, average, and higher) in favor of the lower standard of living, which means that the lower standard of living causes social phobia in comparison to the average and higher living conditions. The researchers developed some recommendations and solutions to address social phobia in students based on the findings of the research.